Mass outdoor events and the spread of an airborne virus: English football and Covid-19 - Olczak, M.; Reade, J. J.; Yeo, M. (University of Reading, 2020)
Mass attendance events are a mainstay of economic and social activity. Such events have public health consequences, facilitating the spreading of disease, with attendant economic consequences. There is uncertainty over the impact such events can have on the spread of disease. We investigate the impact of regular mass outdoor meetings on the spread of a virus by considering football matches in England in February and March 2020 and the spread of Covid-19 into April 2020. There were 340 league and cup football matches with a combined attendance of 1.625m people in March, taking place over 188 of 313 local areas. We look at the occurrence and attendance at matches, and how full the stadia were, and how these variables are related to the spread of Covid-19 in April. We evaluate Covid-19 cases, deaths and excess deaths, all as rates of 100,000 people in an area. We find evidence that mass outdoor events were consistent with more cases and deaths, even after controlling for measurable characteristics of local areas. We find that a football match is consistent with around six additional Covid-19 cases per 100,000 people, two additional Covid-19 deaths per 100,000 people, and three additional excess deaths per 100,000 people. This effect is slightly stronger for the areas of away teams in March, and slightly weaker for matches in February. These results suggest caution in returning to unrestricted spectator attendance at matches. We caveat our analysis though by noting that stadium access and egress routes can be adapted such that some of the opportunities for the spread of an airborne virus could be mitigated. We recommend that the relevant authorities conduct pilot events before determining to what extent fans can return to mass outdoor events.